Health tourism in Malaysia : prospects and challenges - Abd. Manaf, Noor Hazilah (2010)
It is estimated that the health tourism industry in Asia will be worth US$4bil (RM14.2 bil) by 2012, and Malaysia is positioning itself as one of the major players in this region, expecting to earn up to US$590 mil (RM2.1 bil) within five years (The Star, Nov 8, 2008). In 2007 alone, Malaysia received 341,288 medical tourists with revenue of RM253.84 million (www.tourism.gov.my). Thus, the potential of the industry is enormous, and the Malaysian government is making the right strategic move in this direction. Health tourism as is practised and promoted today is a relatively new concept, although patients travelling far and wide in search for medical treatment is not anything new. The paper explores the development and growth of medical tourism in the global context, as well as among the Asian key players in the industry, before moving into the Malaysian experience. The role of key players in advancing the agenda of the industry, namely the Ministry of Health, Ministry of Tourism, Ministry of International Trade and Industry, the Association of Private Hospitals etc, will also be discussed. Finally, challenges faced by an industry still in its infancy will also be discussed.